Experimental behaviour of composite girders with steel undulating web and thin‐walled shear connectors Hilti Stripcon - Motak, Jan; Machacek, Josef (Journal of Civil Engineering and Management, 2004)
Two tests of real‐size composite steel and concrete girders are described. The girders had spans 7,5 m, thin‐walled undulating webs (WT girders) and concrete deck 120/1500 mm concreted into profile steel sheeting TR 60/235/0,75. Thin‐walled shear connectors Hilti Stripcon were used and fastened via powder actuated fasteners. Setup of the tests, relevant instrumentation and measuring procedure are presented. The girder tests supplemented large series of push tests of connectors Stripcon performed at CTU in Prague. One of the composite girders was designed with full‐shear connection while the second one with extremely low partial shear connection (44%). Simple preliminary linear calculations proved that experimental strength capacities of the girders are in good agreement with the calculated values, however, the deflection are due to flexibility of the connectors higher. Buckling shear capacity of the undulating webs in both tests was higher than shear at collapse of the girders. Another test dealing with interaction of web buckling in shear and Stripcon shear connection is under progress. Comparison of theoretical and experimental results is performed and recommendations for practical design are presented. First Published Online: 14 Oct 2010